A STUDY ON PROBLEMS OF ELECTED WOMEN GRAMA PANCHAYATHH MEMBERS DURING GRAMA PANCHAYATHH ELECTION IN DAKSHINA KANNADA DISTRICT - K.R, Ravishankar (International Journal of Research -GRANTHAALAYAH, 2018)
The term development is no meaning without inclusion of all sections of society. Women contribute a lot to the whole society, but it is invisible. Panchayath Raj Institutions, now a day’s equally (elected members) dominated by Women representation. Few important problems have been listed in tools and listed opinion of respondents whether the problem was extreame, moderate or on problem. It helped to understand, which the extreme problem, moderate is and no problem. Majority of the respondents were educated and their age was in-between 28 to 47.Political pressure and problems from political leaders have been identified as the major problems. Remaining problems were minimum. The study was focused on the problems of elected women Grama Panchayathh members during Grama Panchayathh election. The study was descriptive and mainly studied about their social, political and cultural problems. Contents of the questionnaire include respondent’s age, education, marital status and the type of family. Problems during election were divided into three points. First one was no problem, second was about moderate problem and third one was extreme problem.